Pendampingan Pengelolaan Risiko dan Pengendalian Internal Siklus Pengeluaran Kas Desa Sumberejo, Dadapayam, Kabupaten Semarang - Benedicta Sabat Yusdy Supriyanto; Natasha Steffie M. Pellokila; Kaleb Gideon Pengharapan; Agastia Fais Fachrizki; Putri Natalia; Supatmi Supatmi; Ika Kristianti (Universitas Kristen Satya Wacana Salatiga, 2021)
Business processes are related, coordinated and structured activities or tasks. One of the existing business processes in the organization is cash disbursements. The vulnerability of cash management, makes the organization need proper internal control in the process. This community service was carried out in Sumberejo Village to help analyze risk and apply appropriate internal controls in managing cash disbursements. The methods used are interviews, discussions and assistance in making internal identification procedures. This community service resulted in the procedures needed to identify appropriate internal controls for Sumberejo Village. The results of this community service are expected to be able to assist the village in reducing the risk of managing cash disbursements.